2022-RA-376-ESGO Clinicopathological characteristics of 'multiple-classifiers' in endometrial cancer. (20th October 2022) - de Vitis, Luigi Antonio; Schivardi, Gabriella; Bonaldo, Giulio; Fumagalli, Caterina; Raviele, Paola Rafaniello; Achilarre, Maria Teresa; Aloisi, Alessia; Garbi, Annalisa; Lapresa, Mariateresa; Parma, Gabriella; Zanagnolo, Vanna; Aletti, Giovanni Damiano; et al.
Abstract : Introduction/Background: According to the molecular classification, most endometrial cancers(ECs) can be categorised based on a unique molecular signature (e.g., POLE-mutation, mismatch-repair(MMR)-deficiency, p53-abnormality). However, a small number of cases harbour more than one molecular feature and are referred as 'multiple-classifiers'.The aim of the study is to describe the clinicopathological and molecular characteristics of multiple-classifier ECs. Methodology: Among all ECs undergoing a comprehensive molecular analysis at European Institute of Oncology, Milan, between April 2019 and December 2021, 'multiple-classifiers' were identified. Clinicopathological and molecular characteristics were collected from electronic medical records. The molecular analysis consisted of immunohistochemistry for p53 and MMR proteins, microsatellite instability assay, and Next Generation Sequencing (NGS) for POLE exonuclease domain and TP53. ECs were considered p53-abnormal if either immunohistochemistry or NGS resulted altered, MMR-deficient if either proteins expression was abnormal or mismatch-repair instable and POLE when pathogenic POLE mutations were found. ECs were molecularly classified according with WHO-endorsed algorithm. To compare continuous and categorical variables Wilcoxon-Mann-Whitney test and chi-square test were used, respectively. Proportions are reported as number (percentage and 95% confidence interval(CI)). Results: A total of 278 ECs underwent molecular analysis, of which 253 (91.0%, CI 87.8–94.2) harboured a unique molecular signature, while 25 (9.0%, CI 5.8–12.2) were 'multiple-classifiers'. Among them, we identified 15 (5.4%, CI 2.9–8.3) MMRd-p53abn, 6 (2.2%, CI 0.7–4.0) POLEmut-p53abn, 2 (0.7%, CI 0.0–1.8) POLEmut-MMRd, and 2 (0.7%, CI 0.0–1.8) POLEmut-MMRd-p53abn. Clinicopathological and molecular characteristics of 'multiple-classifiers' are shown in table 1 . 'Multiple-classifiers' were more frequently high-grade (56% vs 28%, p=0.003), non-endometrioid (24% vs 10%, p=0.04) ECs when compared to 'single-classifier'( table 2 ). Conclusion: Multiple-classifier ECs represent 9% of the entire study population. Compared to previous studies, the higher proportion of 'multiple-classifiers' could be related to the extensive molecular analysis, comprising the evaluation of both p53 expression and TP53 mutations. More studies addressing the clinical implications on prognosis of 'multiple-classifiers' are needed.